Optimizing Ketamine Infusion Therapy for Treatment‐Resistant Bipolar Depression: Commentary on Zhou et al. (2023) - Chih‐Cheng Lin; Lien‐Chung Wei (Bipolar Disorders, 2026)
ABSTRACT Objectives To contextualize the real‐world findings of repeated intravenous ketamine infusions for treatment‐resistant bipolar depression (TRBPD) and identify priorities for safer, more durable clinical implementation. Methods We provide a focused commentary on Zhou et al. (2023) and integrate selected evidence concerning inflammatory and metabolic correlates, neurocognitive outcomes, and continuation‐phase ketamine treatment. Results Repeated subanesthetic ketamine infusions may rapidly improve depressive and anxiety symptoms with an acceptable short‐term safety profile. However, the predictive value of C‐reactive protein and body mass index varies across cohorts; available cognitive findings are reassuring but limited; and relapse after induction highlights the need for individualized maintenance planning. Conclusions Ketamine pathways for TRBPD should combine cautious patient stratification, repeatable cognitive monitoring, and explicit continuation or booster strategies. Prospective bipolar‐specific studies are needed to clarify predictors, durability, and stopping rules.